Pengaruh Media Diorama Terhadap Hasil Belajar Siswa Pada Materi Siklus Air di Kelas V SDN 52 Banda Aceh - Agus Maulana; Israwati Israwati; Alfiati Syafrina (Universitas Syiah Kuala, 2022)
The Influence of media in the learning process really helps teachers in delivering abstract learning materials to be more real. The formulation of the problem in this study is whether there is an effect of diorama media on student learning outcomes on the water cycle material in class V SDN 52 Banda Aceh. This study aims to prove the effect of diorama media on student learning outcomes on the water cycle material in class V SDN 52 Banda Aceh. the approach in this research is a quantitative approach, using the form of One-Group Pretest-Posttest Design, the approach uses a quantitative approach of pretest and post-test types. The sample in this study were all students in class V SDN 52 Banda Aceh with a total of 14 students, namely 7 boys and 7 girls. Data collection was carried out using a test in the form of answer choices with a total of 20 questions. The results of the study with the acquisition of a score from the mean pretest is 46,07 and the mean post-test score is 74,6 which shows the difference in the learning process without treatment with learning that is given treatment. Based on the data obtained using the SPSS Statistic 22 software, the results obtained a significance (2-tailed) of 0,0000,05. From the results obtained, the decision-making is accepted and rejected. So it can be concluded that there is an influence of diorama media on student learning outcomes on the water cycle material in class V SDN 52 Banda Aceh.